Personal recovery narratives of persons diagnosed with clinical depression - Maximo, Sally I. (Animo Repository, 2020)
Personal recovery in depression may best be understood from an individual and narrative perspective. In this way, the meaning and significance of the personal recovery experience can be explored with greater depth. A focus on personal recovery, rather than on the deficits of the illness, means highlighting strengths which can facilitate movement towards healing and wellness. Using a qualitative-narrative approach, this research explored and analyzed the personal recovery narratives of persons diagnosed with clinical depression. Specifically, it focused on the perceived facilitators of personal recovery, the narrative structure and identity represented in the stories of the participants. The purposive sample consisted of six Filipino adults, two males and four females. All were diagnosed with clinical depression and have reached a certain level of personal recovery. Data was gathered through narrative interviewing and was analyzed and interpreted individually and collectively. As a composite, the perceived facilitators of personal recovery are: a) seeking professional help; b) having an available social support system; c) engaging in activities that promote personal recovery and; d) being responsible for one’s children. With regards to narrative structure, the initial ascent to personal recovery is described as a tentative and slow progression, until a certain stability in personal recovery is reached. The turning points and levels of personal recovery are unique for each participant; however, the movement is towards more solid, stable ground. Reaching stable ground is not seen as a straightforward process. Setbacks may be encountered which could slow down or cause a back slide to the recovery process. Remoteness of diagnosis, anxiety symptoms and personality are identified as factors that could determine variation in reaching stable ground in recovery. Despite varying levels in personal recovery, what is typical in the narratives is the perception of a hopeful future, where the self is envisioned as fulfilled and happy. The narrative identity portrayed is that of someone finding an authentic expression of the self through the personal recovery journey. This striving is achieved through self-differentiation, balance in self-expression and social responsibility. The major areas of inquiry – perceived facilitators of personal recovery, narrative structure and identity – are observed to align with the CHIME recovery processes. As a conclusion, this study provided theoretical contribution by integrating concepts in personal recovery with narrative inquiry. The progression towards personal recovery is simultaneous with a striving for greater authenticity. The construction of an empowered narrative identity supports healing and personal recovery. This research also offered practical implications for use in clinical practice, among persons with mental health issues, in systems providing support and in the direction of future research.